Detection of Yersinia pestis in Sputum by Real-Time PCR - Loïez, Caroline (American Society for Microbiology, 2003)
A 5′ nuclease PCR assay for detection of the Yersinia pestis plasminogen activator (pla) gene in human respiratory specimens with simulated Y. pestis infection was developed. An internal positive control was added to the reaction mixture in order to detect the presence of PCR inhibitors that are often found in biological samples. The assay was 100% specific for Y. pestis. In the absence of inhibitors, a sensitivity of 10(2) CFU/ml of respiratory fluid was obtained. When inhibitors were present, detection of Y. pestis DNA required a longer sample treatment time and an initial concentration of bacteria of at least 10(4) CFU/ml. The test's total turnaround time was less than 5 h. The assay described here is well suited to the rapid diagnosis of pneumonic plague, the form of plague most likely to result from a bioterrorist attack.